2021
DOI: 10.1186/s13756-021-00911-0
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy, virulence determinants and antimicrobial susceptibility of Aeromonas spp. isolated from bacteremia in southeastern China

Abstract: Background The study aimed to elucidate the species taxonomy, clinical manifestations, virulence gene profiles and antimicrobial susceptibilities of Aeromonas strains isolated from life-threatening bacteremia in southeastern China. Methods Clinical samples of Aeromonas causing bacteremia were isolated from a teaching hospital in Wenzhou from 2013 to 2018 and a retrospective cohort study was performed. Aeromonas strains were identified at species le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 20 publications
(14 reference statements)
3
16
0
Order By: Relevance
“…Further investigation of the genetic background of carbapenem resistant isolates in our study revealed a chromosomally encoded metallo-β-lactamase cphA gene, indicating that these clinical isolates are attributed to intrinsic resistance. This finding is in agreement with previously published reports on A. dhakensis isolated from human infections in Australia [ 19 ], Taiwan [ 20 ] and China [ 21 ]. The results suggest that clinical use of carbapenem monotherapy should be considered with caution in order to avoid potential treatment failure and that alternative antimicrobial treatment options, such as fourth-generation cephalosporins, quinolones, amikacin, aztreonam and trimethoprim/sulfamethoxazole, remain active for most A. dhakensis isolates.…”
Section: Discussionsupporting
confidence: 94%
“…Further investigation of the genetic background of carbapenem resistant isolates in our study revealed a chromosomally encoded metallo-β-lactamase cphA gene, indicating that these clinical isolates are attributed to intrinsic resistance. This finding is in agreement with previously published reports on A. dhakensis isolated from human infections in Australia [ 19 ], Taiwan [ 20 ] and China [ 21 ]. The results suggest that clinical use of carbapenem monotherapy should be considered with caution in order to avoid potential treatment failure and that alternative antimicrobial treatment options, such as fourth-generation cephalosporins, quinolones, amikacin, aztreonam and trimethoprim/sulfamethoxazole, remain active for most A. dhakensis isolates.…”
Section: Discussionsupporting
confidence: 94%
“…VITEK MS system was also shown to be insufficient for correctly identifying Aeromonas species. A recent study (26) found that VITEK MS system and housekeeping gene sequencing had a 53.4% coincidence rate.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…in Zhejiang, China, with a fatality rate of 46.15% (26). Aeromonas caviae was the most common strain (34), with a 17% mortality rate in Japan.…”
Section: Aeromonas Dhakensis Was Previously Identified As the Most Co...mentioning
confidence: 99%
“…at room temperature and low temperature (Balakrishna et al, 2010;Janda and Abbott, 2010), and produce virulence factors aerolysin and/or hemolysin (Wong et al, 1998;Heuzenroeder et al, 1999;Balakrishna et al, 2010;Janda and Abbott, 2010). Patients infected with A. hydrophila can develop sepsis and necrotizing fasciitis, which have an acute onset and rapid progression (Tsai et al, 2015;Sun et al, 2021) and are lifethreatening, mainly through ingestion of contaminated water and food and exposed wounds, respectively (Meng et al, 2015); moreover, sepsis can reach a state of systemic toxicity within 24 h (Zhu et al, 2021). In view of these aspects, a rapid, accurate, and sensitive detection method of pathogenic A. hydrophila would contribute to improving the treatment and control strategies and then reducing the hazard of this bacterial infection.…”
Section: Introductionmentioning
confidence: 99%